Texto de lecto-escritura en achuar y castellano : propuesta metodológica para el tercer año de educación general básica. - Kukush Shakaim, Yurank Eduardo (2018)
All this work that I have elaborated is thought, first of all, in my school, where I have done an investigation, and I say that almost in all the schools the same difficulties have been found with Achuar students. What I have done is for the purpose of conserving the Achuar language and ensuring proper use of it in the future. And that way we overcome the difficulties we currently have in Bilingual Education in our Achuar environment, providing material that serves the language and the subsequent development of texts for our schools. Although it is seen that it is a very tiny work, but it has its given and indicated importance, within this work. I have started with the aim of presenting my Achuar students with a text about the use of vowels and consonants in the Achuar language and showing them which are the Spanish speakers, because those are what make them confuse in writing and reading. In order to preserve and ensure proper use of my language, I will begin to work with the family and with the fellow teachers of the different educational establishments so that they are on time making a permanent control, preventing the loans from Spanish to our language. In the future, I will also plan to standardize our language with the specific goal of having standardized Achuar language support material, unifying many dialects in the area.